Computer in the Medical Office - M. Sanderson Susan (MC Graw Hill, 2009)
Computers in the Medical Office 6e is the best-selling text for training students using full-featured and current Medisoft Version 14 Patient Billing software. McGraw-Hill publishes the most titles to train students on Medisoft software. Our publishing relationship with Medisoft has been ongoing for 15 years. Computers in the Medical Office 6e offers medical office training using current, realistic medical office cases while building transferable computerized medical billing and scheduling skills. Students who complete this course will learn the appropriate terminology and skills to use any patient billing software program with minimal additional training. As students progress through Medisoft, they learn to gather patient information, schedule appointments and enter transactions. The practical, systematic approach is based on real-world medical office activities. Go with the best. Go with the tried and true. Go with the Medisoft titles that will give you and your students the training and support you need to be successful. Go with McGraw-Hill's Computers in the Medical Office 6e.